Association between neutrophil to lymphocyte ratio and the mortality of patients with sepsis: an update systematic review and meta-analysis - Gao, Zimo; Wang, Xiaolei; Wang, Wenfeng; Kang, Zhichen; Chen, Xinghai (Frontiers in Medicine, 2025)
ObjectivesTo present the most up-to-date systematic review and meta-analysis assessing the relationship between the neutrophil-to-lymphocyte ratio (NLR) and mortality in individuals diagnosed with sepsis.MethodsWe conducted a systematic literature retrieval via PubMed, Embase, Web of Science, and Cochrane Library until March, 2025 for studies which evaluated the link between NLR and the mortality of patients with sepsis. Odds ratios (OR) and 95% confidence intervals (CI) were used for data pooling. In addition, sensitivity analysis and subgroup analysis were performed to examine the stability of the results and potential sources of heterogeneity. All analyses were performed using Review Manager 5.4 and STATA 15.1.ResultsA total of 21 studies including 23,621 patients were incorporated into the meta-analysis. The results demonstrated a significantly higher mortality (OR: 1.11; 95% CI: 1.08, 1.14; p<0.00001) in the group with high NLR compared with the group with low NLR. The sensitivity analysis confirmed the stability of this result. In addition, subgroup analysis by cut-off and sample size showed that the predictive value of NLR for mortality was still significant in all subgroups (p < 0.05).ConclusionNLR was significantly associated with the risk of death in individuals diagnosed with sepsis. The higher the NLR, the higher the risk of death. Considering the potential publication bias and inevitable heterogeneity of this study, further large-sample, multicenter, prospective clinical studies are needed in the future to verify the exact link between NLR and the risk of death in patients with sepsis.Systematic review registrationOur systematic review has been registered in the International Prospective Register of Systematic Reviews (PROSPERO). The unique identifier is CRD420251050651, and the publicly accessible URL is https://www.crd.york.ac.uk/PROSPERO/view/CRD420251050651.